76. THE ROLE OF FRAILTY IN PREDICTING POSTOPERATIVE SOCIOECONOMIC OUTCOMES AMONG PATIENTS WITH METASTATIC BRAIN CANCER. (4th August 2020) - Khalafallah, Adham M; Jimenez, Adrian E; Huq, Sakibul; Patel, Palak; Mukherjee, Debraj
Abstract: BACKGROUND: Patient frailty is an important consideration in the context of providing high-value, cost-effective care, as it has shown to effectively predict postoperative morbidity and mortality in many surgical subspecialties. However, for metastatic cancer patients, there is a lack of consensus as to whether frailty effectively predicts postoperative outcomes such as survival and length of stay (LOS), specifically among patients with metastatic brain tumors. OBJECTIVE: The present study sought to determine if the 5-factor modified frailty index (mFI-5) independently predicts LOS, discharge disposition, and total hospital charges among patients with metastatic brain cancer. METHODS: Patients diagnosed with metastatic brain cancer who underwent surgery between 2017–2019 at a single academic institution were analyzed. Bivariate analysis identified patient characteristics significantly associated of LOS, discharge disposition, and total hospital charges. Multivariate linear regression was used to identify independent predictors of LOS and total hospital charges, while multivariate logistic regression was used to identify independent predictors of non-routine discharge disposition. P <0.05 was considered statistically significant. RESULTS: A total of 302 patients were included in our analysis. Our patient cohort had a mean age (standard deviation) of 62.27 11.86 years, and was majority female (52.0%) and Caucasian (74.2%). The majority of patients had a primary lung cancer (24.8%), followed by breast cancer (13.6%). There was no significant difference in mFI-5 score between patients with metastatic tumors of known origin compared to patients with metastatic tumors of unknown origin (p=0.61). In multivariate analysis, a higher mFI-5 score independently predicted longer LOS (regression coefficient [Coef]=1.36 days, p<0.001), non-routine discharge disposition (odds ratio [OR]=1.60, p=0.0079), and higher total hospital charges (Coef=4325.54, p=0.0010). CONCLUSION: The mFI-5 independently predicts LOS, discharge disposition, and total hospital charges among our cohort of metastatic brain cancer patients. Our findings may be used to aid physicians in providing high-value neurosurgical care.